EXPERIMENTAL DEMONSTRATION OF ELECTRICAL POWER GENERATION USING STATIONARY EXERCISE BICYCLE COUPLED WITH WIND TURBINE REGULATOR - Abubakar, Isiyaku; Olaleke, Isaac B.; Kadandani, Nasiru B. (FUDMA JOURNAL OF SCIENCES, 2024)
The small power generation using exercise bicycle is one of the current areas patronized by researchers. This is due to the two major benefits obtainable from the exercise machine, the benefit of exercising one’s body and the utilization of electrical power generated. Wind turbine regulator is specifically designed to regulate the output voltage of a wind turbine generator, which is characterized by varying speed and hence varying output power. The exercise bicycle driven alternator has a similarity with wind turbine generator in terms of variable speed, especially when ridden by different personalities. This paper demonstrates how small power can be generated using exercise bicycle. Further, the paper analyzes the performance of the by regulating its output using small wind turbine regulator. The result shows that, a regulated output within the range of 12V is obtained for all the tested loads, which makes the system more compatible with all types of 12V DC loads. Also the excitation voltage of the machine is improved from 4.5V (1.22A) using the diodes rectifier to 2.5V (0.81A) when the wind turbine regulator is used. With the improved power generation in this work the exercise bicycle will be a better alternative source for small power generation which can be used in DC lightings, DC fans, charging batteries and laboratory experiments.
Keywords: Stationary bicycle; automotive alternator; wind turbine regulator; voltage regulation; RPM